Workplace Hygiene Practice among Saloon Workers in Bangladesh Army (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: In Bangladesh like any other developing country, saloon is the unique place for transmission of some communicable diseases.Objectives: To explore the level of knowledge, attitude and practices regarding hygienic and cleanliness among saloon workers of Bangladesh Army.Materials and Methods: This descriptive cross-sectional study was carried out in different barber shops of army units in Dhaka cantonment during the month of May 2011. Data were collected from 115 saloon worker by structured questionnaire through face to face interview.Results: Mean age of 115 respondents’ was 22.65±5.8 years whereas 76% of the respondents have less than 5 years of service. Their monthly income was less than 8000 taka and 70.4% had only primary education. About 77% washed linen used for wrapping twice a week and 16.5% did it in alternate day. About 89.5% had awareness and knowledge of transmission of skin diseases through unclean comb, but only 2.6% did not have any knowledge regarding this matter. In case of disease spread through unclean handle of blade/khur majority 60% respondents were aware about skin disease but only 12% were aware about AIDS and 16.5% were aware about jaundice. Majority (90%) found using antiseptic solution to clean used shaving brush /handle of razors. No respondent clean their hand before providing service to each customer and none used fresh linen for each customer rather 1 linen for every 10-12 customer on average.Conclusion: The study revealed that majority of the saloon workers were either illiterate or had only primary plus level education with poor socio economic background. Despite the knowledge and practice of workplace hygiene among the saloon workers are quite satisfactory levels even though there are areas for further improvement.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 79-80